2020
DOI: 10.5114/ait.2020.101844
|View full text |Cite
|
Sign up to set email alerts
|

Occupational hazards in anaesthesiology during the COVID-19 pandemic

Abstract: According to the Occupational Safety and Health Administration of the Department of Labor of the United States, the exposure risk for anaesthesiologists working with COVID-19 patients can be classified as high or very high. This is mostly due to fact that the anaesthesiologists work in close contact with patients’ airways, and the aerosol-generating nature of some procedures they perform. Fortunately, despite the occupational hazard, the incidence of COVID-19 among anaesthesiologists and intensivists remains r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Exposure to AGP was associated with a decreased risk of SARS-CoV-2 positivity at NPS (p = 0.02), although this result was not confirmed ay univariable and multivariable logistic regression analysis in the present study. Nevertheless, the latter finding has already been thoroughly investigated in the open literature [6][7][8][9]13,14,21,42]. AGPs are commonly associated with a high risk of respiratory viruses' infection [21]: a systematic review and meta-analysis on 17 studies reported an OR of SARS-CoV-2 infection of 6.69 for endotracheal intubation, 3.65 for Non-Invasive Ventilation and 10.03 for nebulized medications [9].…”
Section: Interpretation Of Findings In Relation To Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to AGP was associated with a decreased risk of SARS-CoV-2 positivity at NPS (p = 0.02), although this result was not confirmed ay univariable and multivariable logistic regression analysis in the present study. Nevertheless, the latter finding has already been thoroughly investigated in the open literature [6][7][8][9]13,14,21,42]. AGPs are commonly associated with a high risk of respiratory viruses' infection [21]: a systematic review and meta-analysis on 17 studies reported an OR of SARS-CoV-2 infection of 6.69 for endotracheal intubation, 3.65 for Non-Invasive Ventilation and 10.03 for nebulized medications [9].…”
Section: Interpretation Of Findings In Relation To Other Studiesmentioning
confidence: 99%
“…Nurses, HCWs working in hospitalization/emergency wards and infectious diseases personnel seem to have the highest risk of infection, with ob-gyn personnel and pediatrics personnel having the lowest risk [10][11][12]. By contrast, the evidence regarding anesthesiologist/intensivists is inconclusive [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…CVP should be monitored in cases of shock, circulatory failure, massive infusion or transfusion requirement, situations with massive bleeding risk, situations where careful fluid resuscitation is a must such as in paediatric patients or patients with cardiac problems. [5] CVP is a value indicating right atrial pressure or right ventricular filling pressure. It is an indicator of intravascular fluid status and right heart function.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with left ventricular ejection fraction <40%, severe tricuspid regurgitation, mitral and aortic stenosis, pulmonary hypertension. 5. Patients with pericardial effusion and pleural effusion.…”
Section: Patients With Intra-abdominal Tumoursmentioning
confidence: 99%